2022
DOI: 10.1364/oe.476166
|View full text |Cite
|
Sign up to set email alerts
|

Strong enhancement of Goos–Hänchen shift through the resonant optical tunneling effect

Abstract: The resonant optical tunneling effect (ROTE) originates from the frustrated total reflection effect because unique transmission characteristics are used to study high-sensitivity sensors. In this study, we theoretically demonstrated that choosing a suitable transmission gap made it possible for the ROTE structure based on hexagonal boron nitride and graphene to obtain a large Goos–Hänchen shift as high as tens of thousands of times the incident wavelength at a specific incident angle. The amplitude of the Goos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…The theoretical studies such as Refs. 24, 3537 have reported shifts in heterostructures that could be positive or negative using different materials at different angles of radiation. However, they do not include a discussion on the reason.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The theoretical studies such as Refs. 24, 3537 have reported shifts in heterostructures that could be positive or negative using different materials at different angles of radiation. However, they do not include a discussion on the reason.…”
Section: Resultsmentioning
confidence: 99%
“…The configuration considered in Ref. 37 used the resonant optical tunneling effect and consisted of two dielectric prisms with an air gap between them separated by two hBN dielectric layers, with the bottom of each prism coated with graphene. This symmetrical structure, with an air gap width of 250 μm and an hBN thickness on both sides of 10 nm, yielded a GH shift of 2500 λ.…”
Section: Introductionmentioning
confidence: 99%
“…In [9], a device was proposed for the spatial separation of an incident white light beam into three color beams. The resonant optical tunneling effect based on FTIR leads to a strong enhancement of the Goos-Hanchen shift of the light beam in graphene and plasmonic metasurfaces [10][11][12][13][14][15]. In [16], the effect of frequency dispersion in the resonator layer on the FTIR process is considered.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomena has been shown to occur in various configurations and materials such as photonics crystals [10][11][12] , dielectric slabs 6,13 , and metamaterials [14][15][16] . It has also been investigated at the interface of Weyl semimetals 17,18 and in structures containing graphene [19][20][21][22][23][24] . In a recent study, giant GH shift has been demonstrated to occur at the interface of PT-symmetric bilayer structure due to surface modes 25 .…”
mentioning
confidence: 99%